Students' Mathematical Communication Skills in the Ethnomathematics PBL Model Assisted by Wordwall - Fitrotun Nisa; Yus M. Cholily; Siti Khoiruli Ummah (University of Muhammadiyah Malang, 2026)
Background: Mathematical communication skills are positively correlated with students' problem-solving skills, so the development of these skills needs to be carried out in the learning process. Skill development can be successful through the implementation of a suitable learning model. Objectives: This study aims to analyze students' mathematical communication skills and problem-solving skills in learning math problems in the Problem Based Learning (PBL) model assisted by wordwall. Methods: This research is a qualitative study using descriptive methods. The subjects were 17 eighth-grade junior high school students in Malang, Indonesia. Results: Based on the results of data analysis through research instruments in the form of data collected from student response questionnaires to the use of learning media, the transformation geometry discussion test related to students' mathematical communication skills and problem-solving skills. From the results of the study, it was concluded that the use of their Problem Based Learning (PBL) model and wordwall media for students' mathematical communication skills with an average percentage of 82.82%, and students' problem-solving skills were in the high category with a rate of 84.88%. Conclusions: The PBL model, supported by wordwall recommendations, is an innovative alternative to improve students' mathematical communication in geometry and can be further developed in other topics and digital learning platforms curriculum in an effort to build student competency.